IMPROVING THE ABILITY TO WRITE SCIENTIFIC NAMES OF ANIMALS USING FLASH CARD MEDIA FOR GRADE 5 ELEMENTARY SCHOOL STUDENTS - Sahri Nova Yoga, Layil Safitri (STAI Syaichona Moh. Cholil Bangkalan, 2025)
This activity is based on the importance of early introduction to English, especially in understanding basic concepts such as living things, which at the same time increases science literacy. This service activity aims to increase students' understanding of living things through United Kingdom flashcard media. The method of implementing the activity includes the creation and distribution of flashcard media, training in the use of flashcards through direct assistance in learning activities. Students are introduced to different types of living things through pictures accompanied by names in English. The teaching and learning process also involves interactive activities to strengthen understanding and mastery of vocabulary. The results of the activity showed a significant increase in vocabulary related to living things, qualitatively. This activity is expected to be an innovative and sustainable learning model in elementary schools